As encruzilhadas de sincretismo, transe, gênero e sexualidade em dois terreiros de umbanda de São Carlos-SP - Pinto, Bryan Henrique (2025)
Umbanda is a religion marked by religious syncretism, sometimes with more Catholic and Spiritist elements, closer to the “pole of the cross”, sometimes with more Africanized elements, closer to the pole of the crossroads. In effect, this research was structured to understand heterosexual men’s refusal of trance with female entities, specifically with the Pombagira. The analysis focused on the specificity of trance as a moment in which gods, entities and humans are tied together in plots involving sex, gender and desire. Through ethnographic research carried out in umbanda temple in the city of São Carlos, one of the traditional line, linked to the Federação Umbandista do ABC, and another of the omolocô line, closer to African practices. Subsequently, semi-structured interviews were conducted with the priests and mediums of the temples. This data was analysed taking into account the religious trajectory of the interviewees and the religious syncretism and the syncretic habitus present in them. The work presents the multiple Umbanda representations of syncretism, considering that all religions are syncretic. In the context of Afro-Brazilian religions, this social phenomenon has produced transformations of Èṣù, the orisha of communications, into two halves, with the male side remaining with the exus catiços and the female side with the Pombagiras. Religious works were also analysed, especially books by Ronaldo Linares, president of the Federação do ABC and an important Umbanda leader, being a continuator of Zélio de Moraes in the state of São Paulo. In order to understand the representation of the feminine in Umbanda: on the one hand, the Orishas, who underwent a process of Christianization with syncretism, losing the African elements associated with sexuality, and on the other, the Pombagiras, representing transgressive sexuality, elements that have consequences for the relationship with the trance and the masculinity of the mediums. Various studies on the relationship between sexuality and Afro-Brazilian religions point to the pole of the crossroads, specifically Candomblé, as being more open to dissident sexualities, especially considering the relationship between the trance and the deities. This study aims to fill the gap in Umbanda's relationship with gender and sexuality issues. In effect, it was possible to contribute to a greater understanding of the Umbanda universe and the relationship between the entities and the subjectivity of the mediums.